ANALYSIS OF DYNAMICS AND SOURCES OF MANGANESE, COPPER, NICKEL AND ALUMINUM IONS FOUND IN THE TRANS-BORDER MIUS RIVER DURING THE PERIOD FROM 2003 TO 2017 - E. V. Vorobyov; E. V. Usova; Yu. V. Orekhova (Юг России: экология, развитие, 2019)
Aim. Transboundary rivers are complex enough to study which requires analysis of not only the polluting agents themselves but also geographic features and specifics of economic activities. The work is devoted to the study of the dynamics of pollution of the Mius River with ions of manganese, copper, nickel and aluminum, taking into account the peculiarities of the regions through which the river flows and the specifics of the anthropogenic load on the adjacent territories.Material and methods. The article considers some natural and anthropogenic factors that determine the increased content of metal ions in the transboundary river Mius, taking into account the peculiarities of the territory of the river. Based on the monitoring data from 2003 to 2017, the dynamics of river pollution by aluminum, manganese, copper and nickel were presented; monthly averages for the period under review were also given.Results. It is revealed that pollution has an annual periodicity which depends on natural factors and metallurgical industry, characteristic of Donbass. The negative effect of these metals on human health and environment was indicated.Conclusion. There is a connection between changes in concentrations of the metals of concern, which indicates the predominance of the anthropogenic source of metals over natural in the Mius River.